Fever of unknown origin associated with immune checkpoint inhibitors - Tong, Xu; Zhan, Tao; Dong, Xiaoqin; Xu, Dong (Frontiers in Immunology, 2024)
Since the approval for the treatment of melanoma in 2014, immune checkpoint inhibitors (ICIs) have revolutionized the therapy pattern across various malignancies. Coinciding with their frequent usage, their adverse effects, including fever, cannot be neglected. In the context of cancer diseases and cancer treatments, fever of unknown origin (FUO), which has long posed a challenge for clinicians in terms of diagnosis and management, brings forth new connotation and significance. In this paper review, we present the concept of ICIs-associated FUO, consider activated immune system and elevated cytokines as common mechanisms by which ICIs induce fever and various immune-related adverse events (irAEs), summarize and compare the primary aetiologies of ICI-associated FUO, and compare it with conventional types of FUO.